2008
DOI: 10.1002/jpln.200700302
|View full text |Cite
|
Sign up to set email alerts
|

Repeated drying–rewetting cycles and their effects on the emission of CO2, N2O, NO, and CH4 in a forest soil

Abstract: Prolonged summer droughts due to climate change are expected for this century, but little is known about the effects of drying and wetting on biogenic trace‐gas fluxes of forest soils. Here, the response of CO2, N2O, NO, and CH4 fluxes from temperate forest soils towards drying–wetting events has been investigated, using undisturbed soil columns from a Norway spruce forest in the “Fichtelgebirge”, Germany. Two different types of soil columns have been used for this study to quantify the contribution of organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 34 publications
10
54
1
Order By: Relevance
“…Almost immediate increase in respiration after rewetting has been recorded by others (e.g., Borken et al 2003), though recovery of CO 2 respiration to optimal levels may also take a few days (Muhr et al 2008). Secondary peaks or oscillation periods of CO 2 respiration, as observed for the MO incubations, have also been reported by Clein and Schimel (1994) for birch litter that was kept moist after an initial drying.…”
Section: Respiration and Net N Mineralization Responses To Wettingsupporting
confidence: 61%
“…Almost immediate increase in respiration after rewetting has been recorded by others (e.g., Borken et al 2003), though recovery of CO 2 respiration to optimal levels may also take a few days (Muhr et al 2008). Secondary peaks or oscillation periods of CO 2 respiration, as observed for the MO incubations, have also been reported by Clein and Schimel (1994) for birch litter that was kept moist after an initial drying.…”
Section: Respiration and Net N Mineralization Responses To Wettingsupporting
confidence: 61%
“…The rapid decreases in oxygen availability caused larger emissions of N 2 O by denitrification (Kester et al 1997). In addition, drying-rewetting alternation could restrict reduction of N 2 O to N 2 through further denitrification, and led to more N 2 O production, so the post precipitation N 2 O fluxes were usually high (Muhr et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…It is, however, very common in climates with distinct dry seasons or more prolonged dry periods (Doerr et al, 2003;Doerr and Moody, 2004;Leighton-Boyce et al, 2005;Stoof et al, 2011) and may become more common in the UK in the future climate predictions (IPCC, 2013). It is also an important scenario to be considered during the rewetting of extremely waterrepellent soils after drought, as reported by Muhr et al (2008Muhr et al ( , 2010, who observed a slower regeneration of CO 2 fluxes following wetting that could have been caused by SWR.…”
Section: Effect Of Soil Moisture and Swr On Soil Co 2 Fluxesmentioning
confidence: 96%